Inteligencia emocional y vínculos parentales en niños de la escuela “Dr. Camilo Gallegos Domínguez” de la ciudad de Machala, en el periodo lectivo 2014-2015. - Chávez Aguirre, Sandra Priscilla (2015)
By conducting this research aims to verify, first, the lack of skills of emotional intelligence in children 7th grade school "Dr. Camilo Gallegos Dominguez "in the city of Machala and its possible relation to the lack of school effectiveness. Later there is a need to implement an emotional education program in the aforementioned school, which in turn could serve as a reference for creating such programs at various educational establishments in our region.